1969
DOI: 10.1111/imj.1969.18.3.222
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Alcoholic Cirrhosis

Abstract: Seventy-seven alcoholic patients, 54 men and 23 women, had cirrhosis of the liver when they first attended the Alcoholism Clinic at St Vincent 's Hospital, Melbourne, between July, 1964, and June, 1968. During this period Soo chronic alcoholics, 663 men and 137 women, attended the clinic. Cirrhosis was thus diagnosed twice as often in women as in men.The case histories of the 77 cirrhotic patients were reviewed, and information was collected about socio-economic status and drinking habits. This information w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

1975
1975
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 16 publications
3
18
0
2
Order By: Relevance
“…A large North American study of over 22,000 also showed that daily drinking carried more than twice the risk of liver damage compared with intermittent drinking once or twice per week [28]. Other studies have drawn similar conclusions [7,9,[29][30][31][32][33][34][35]; and our own study in Southampton, UK, showed that from 80 patients with severe ALD only one reported a consistent pattern of binge drinking [8], the rest were daily or near-daily drinkers. The study also highlighted that risky drinking patterns reported by ALD patients may be established in their early twenties -patients with alcohol-related liver disease were found to have drunk more heavily and more frequently when in their early twenties.…”
Section: Emma Brandishsupporting
confidence: 64%
“…A large North American study of over 22,000 also showed that daily drinking carried more than twice the risk of liver damage compared with intermittent drinking once or twice per week [28]. Other studies have drawn similar conclusions [7,9,[29][30][31][32][33][34][35]; and our own study in Southampton, UK, showed that from 80 patients with severe ALD only one reported a consistent pattern of binge drinking [8], the rest were daily or near-daily drinkers. The study also highlighted that risky drinking patterns reported by ALD patients may be established in their early twenties -patients with alcohol-related liver disease were found to have drunk more heavily and more frequently when in their early twenties.…”
Section: Emma Brandishsupporting
confidence: 64%
“…58 Many casecontrol studies and case series of patients with liver disease or alcohol dependence have also suggested increased sensitivity of women to the deleterious effects of alcohol on the liver. 30,[114][115][116][117][118][119][120] Postmenopausal women with cirrhosis have elevated estrogen and decreased testosterone levels that appear to correlate with the severity of liver disease. 121 One casecontrol study suggested that reproductive hormone levels may have prognostic value for women with end-stage alcohol-related liver disease.…”
Section: Medical Risks Of Drinking For Women Compared With Menmentioning
confidence: 99%
“…The incidence of AC varies worldwide, ranging from 6 to 40% of people drinking more than 160 g of alcohol every day for at least 5 years [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. This data indicate that not every person abusing alcohol will develop the disease, suggesting that genetics, in combination with environmental factors, plays an important role in the development of AC.…”
Section: Introductionmentioning
confidence: 99%